Genome-Wide Comparative Functional Analyses Reveal Adaptations of Salmonella sv. Newport to a Plant Colonization Lifestyle - de Moraes, Marcos H.; Soto, Emanuel Becerra; Salas González, Isai; Desai, Prerak; Chu, Weiping; Porwollik, Steffen; McClelland, Michael; Teplitski, Max (Frontiers in Microbiology, 2018)
Outbreaks of salmonellosis linked to the consumption of produce have been disproportionately associated with the strains of serovar Newport. A hypothesis that strains of sv. Newport have evolved unique adaptations to persistence in plants that are not shared by other serovars was tested. We used a genome-wide mutant screen to compare growth in tomato fruit of a sv. Newport strain from an outbreak traced to tomatoes, and a sv. Typhimurium strain from animals. Most genes in Salmonella sv. Newport that were selected during persistence in tomatoes were shared with, and similarly selected in S. Typhimurium. Many of these functions are involved in basal metabolism, including amino acid biosynthetic pathways, iron acquisition, and maintenance of cell structure. One exception was a greater need for the core genes involved in purine metabolism in sv. Typhimurium than in sv. Newport. A gene, papA, that was unique to sv. Newport, contributed to the fitness in tomatoes. The papA gene was present in the sv. Newport Group III genomes, was generally absent from other Salmonella genomes, but its homolog was detected in Pantoea, Dickeya and Pectobacterium, members of the Enterobacteriacea family that can colonize both plants and animals.